Head-coach turnover and the performance of football teams in Brazil - Azevedo, Caio Oliveira (2021)
This studies aims to evaluate the consequences of in-season changes of head-coach on the performance. Data from nine seasons were used, with turn-by-turn team result indicators and bookmaker information. From the estimates obtained, improvement in several measures of performance after the substitution of coach was noticed, considering the game following the change. However, this effect turns out to be statistically insignificant, when analyzed on a larger number of games after the change. Thus, it turns out that the change of coach does not show itself as an effective strategy to improve performance.